Sociodemographic Determinants of Youth NEET in Indonesia - Rahmad Hidayat; Taufiq C. Dawood; Muhammad Abrar (Grimsa Journal of Business and Economics Studies, 2026)
Indonesia’s youth NEET (Not in Education, Employment, or Training) rate has consistently exceeded 20 percent since 2018, indicating a substantial loss of productive human capital and posing serious socio-economic challenges that require structural policy responses. This study examines the sociodemographic factors associated with NEET status among individuals aged 15–24 in Indonesia, while also investigating the role of socio-digital factors that remain underexplored in existing research. Using data from the 2023 National Labor Force Survey (SAKERNAS) and a sample of 158,816 youth, the analysis employs binary logistic regression to assess the effects of individual characteristics (gender, age, marital status, disability, and education), household characteristics (education and marital status of the household head), and socio-digital factors (technology access and participation in government programs) on the probability of being NEET. The findings demonstrate that NEET status in Indonesia represents a complex and multidimensional problem, with an estimated prevalence of approximately 24.3 percent and strong influences from sociodemographic factors. Higher educational attainment, unmarried status, and prior work experience are associated with a lower likelihood of being NEET, whereas access to information technology and higher educational attainment of the household head are linked to a higher risk. These results underscore the need for an integrated and context-specific policy strategy that combines employment creation, enhancement of vocational education quality, strengthening of digital skills, and family planning initiatives, while accounting for regional disparities.